DATABASE APPLICATIONS UTILIZATION IN PRACTICE - T (Интеллектуальные системы в производстве, 2009)
Databases are now used resource for support of planning and controlling activity in various application areas. Outplanting evidence system, including modules for input, updating, revision and output, was suggested and realized for Borova hora arboretum (scientific-pedagogic workstation of Technical university in Zvolen), with important data and information as endangered species and outplanting.